PERBEDAAN TINGKAT KEDISIPLINAN SISWA ANTARA YANG MENGIKUTI DAN YANG TIDAK MENGIKUTI EKSTRAKURIKULER PENCAK SILAT (STUDI PADA SISWA KELAS VII - IX SMP BAHRUL ULUM, SURABAYA) - MAHUDA, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Extracurricular is one of medium that helps students to improve physical fitness and health along values of sportsmanship student in school other than physical education. Moreover, extracurricular help to shape student character. One of the value which taught in extracurricular is discipline. Pencak silat extracurricular is one of the activity that instill sportsmanship value. With embeded discipline value for student is expected to make them obey the rules that exist, either in school or society and students who have good discipline will make the process of teaching and learning at school will be better since the student have learning discipline, school discipline also self discipline. This study is aimed to find out the difference between level of student discipline who comply and those who not comply pencak silat extracurricular in Bahrul Ulum Junior High School Surabaya also to find out student discipline, including the sub-dimension in terms of the duration they comply in this extracurricular. This study uses non-experimental study with a survey approach. Subject in this study were 68 students of VII-IX grader in Bahrul Ulum Junior High School with purposive sampling and purposive random sampling technique. The instrument is in a form of questionnaire with data analysis technique using t-test and product moment correlation. According to analysis using t-test obtained value tcount 4,266 > ttable 1,665 that Ha is accepted and H0 rejected. Whereas, at the correlation count obtained at 0,347 consulted with rtable with degress of freedom 34 – 2 = 32, with significant level of 5% is obtained rtable at 0,339. Determination coeficient from rcount 0,347 is 12,06%. That is known the value rcount0,347 > rtable 0,399 so it is said that there is a significant relationship. It can be concluded that there are significant differences between the level of discipline of student who comply and those who not comply in pencak silat extracurricular in Bahrul Ulum Junior High School Surabaya. While in terms of the duration of complying the extracurricular is having a significant relationship as well. Where the level of discipline also being effected with the duration of complying this extracurricular is 12,06%, while 87,94% is being effected by other factor that are not included in this study. In addition, based on the sub-dimension, timeliness aspect and social behavior aspect also have a significant relationship, but for dressing standard and ethics study aspect has no a relationship. Keywords: student discipline, pencak silat extracurricular